Some aspects of photocatalytic reactor modeling using computational fluid dynamics - Boyjoo, Yash; Ang, Ha-Ming; Pareek, Vishnu (Pergamon, 2013)
Design and analysis of photoreactors is significantly more challenging than conventional reactors due to participation of radiation in chemical reactions. This problem is further compounded in case of photocatalytic reactors because of presence of photocatalytic particles, which not only produce complex light scattering effects but, in case of slurry systems, also act as an additional phase, the hydrodynamics of which is essential to characterize for evaluating the phase distribution of photocatalyst particles without which it is not possible to calculate the light intensity distribution. This then necessitates the use of a computational fluid dynamics (CFD)-based simulation approach which can simultaneously take into account the hydrodynamics of multiple phases, light intensity distribution and reaction kinetics. This paper presents a sequential review of all steps for CFD simulations of photocatalytic reactors. The hydrodynamic modelling has been considered first with an emphasis on the Eulerian–Eulerian model because of its ability to handle large-scale photocatalytic reactor systems with only relatively moderate computational resources. This has been followed by a review of lamp emission models, which in CFD models are used as boundary conditions for solving the radiation transport equation (RTE). Before discussing the kinetics of photocatalytic reactors, are view of numerical models for solving the RTE has also been presented for both slurry and immobilized reactor systems. Finally, the paper discusses important factors for setting up the boundary conditions for CFD modeling of photocatalytic reactors.